Segmental Colonic Resection Is a Safe and Effective Treatment Option for Colon Cancer of the Splenic Flexure: A Nationwide Retrospective Study of the Italian Society of Surgical Oncology–Colorectal Cancer Network Collaborative Group. Issue 10 (October 2020) - Degiuli, Maurizio; Reddavid, Rossella; Ricceri, Fulvio; Di Candido, Francesca; Ortenzi, Monica; Elmore, Ugo; Belluco, Claudio; Rosati, Riccardo; Guerrieri, Marco; Spinelli, Antonino; De Nardi, Paola; Cianflocca, Desiree; et al.
Abstract : BACKGROUND: Global experience with splenic flexure cancer is limited because of its low incidence. Both limited (segmental) and extended resections are performed, because agreement on which is the adequate procedure has not been reached. OBJECTIVE: The purpose of this study was to investigate whether segmental resection is as safe and effective as extended resection. DESIGN: This nationwide retrospective cohort study included all consecutive resections of splenic flecure cancer between January 2006 and December 2016 using data from the National Colorectal Cancer Network of the Italian Society of Surgical Oncology following the guidelines set out in the STROBE statement. SETTING: Data were obtained for 31 Italian Referral Centers for Colorectal Surgery. PATIENTS: A total of 1304 patients were submitted to resection of the splenic flexure (n = 791, 60.7%) or extended procedures (extended right and left colectomies; n = 513, 39.3%). MAIN OUTCOME MEASURES: We evaluated Clavien-Dindo ≥3 postoperative complications and oncological (number of lymph nodes removed, length of free proximal and distal margins, rate of R0 resections) and survival outcomes. RESULTS: The 2 arms were well balanced in regard to sex, BMI, ASA and Eastern Cooperative Oncology Group scores, and disease stage. Limited resection was performed more frequently using a minimally invasive approach (62.1% vs 50.9%, p < 0.001) and with shorter operation times than extended procedures (165 vs 189 minutes, p < 0.001), but the same Clavien-Dindo ≥3 postoperative complications (6.44% vs 6.43%, p = 0.99), 30-day mortality (0.63% vs 0.38%), oncological outcomes, and survival rates (5-year overall survival 0.84 vs 0.83, 5-year progression-free survival 0.85 vs 0.84). LIMITATIONS: There are limitations inherent to the retrospective nature of the study and a potential lack of consistency in treatment across centers over time. Indications as to why a specific operation was chosen were based mostly on surgeons' beliefs. CONCLUSIONS: Segmental resection is a safe and effective treatment option for cancer of the splenic flexure. See Video Abstract at http://links.lww.com/DCR/B307 . LA RESECCIÓN DE COLON SEGMENTARIA ES UNA OPCIÓN DE TRATAMIENTO SEGURA Y EFICAZ PARA EL CÁNCER DE COLON DE LA FLEXIÓN ESPLÉNICA: UN ESTUDIO RETROSPECTIVO A NIVEL NACIONAL DE LA SOCIEDAD ITALIANA DE ONCOLOGÍA QUIRÚRGICA - GRUPO COLABORATIVO RED DE CÁNCER COLORRECTAL: ANTECEDENTES: La experiencia global con el cáncer de flexión esplénica es limitada debido a su baja incidencia. Se realizan resecciones limitadas (segmentarias) y extendidas, ya que no se ha llegado a un acuerdo sobre cuál es el procedimiento adecuado. OBJETIVO: El propósito de este estudio fue investigar si la resección segmentaria es tan segura y efectiva como la resección extendida. DISEÑO: Este estudio de cohorte retrospectivo a nivel nacional incluyó todas las resecciones consecutivas de cáncer de flecura esplénica entre enero de 2006 y diciembre de 2016 utilizando datos de la Red Nacional de Cáncer Colorrectal de la Sociedad Italiana de Oncología Quirúrgica siguiendo las pautas establecidas en la declaración STROBE. ENTORNO CLINICO: Se obtuvieron datos para 31 centros de referencia italianos para cirugía colorrectal. PACIENTES: Un total de 1304 pacientes fueron sometidos a resección de la flexión esplénica (n = 791, 60.7%) o procedimientos extendidos (colectomías extendidas derecha e izquierda; n = 513, 39.3%). PRINCIPALES MEDIDAS DE VALORACION: Evaluamos Clavien-Dindo ≥3 complicaciones postoperatorias y oncológicas (número de ganglios linfáticos extirpados, longitud de márgenes proximales y distales libres, tasa de resecciones R0) y resultados de supervivencia. RESULTADOS: Los dos brazos estaban bien equilibrados en cuanto a sexo, IMC, ASA y puntajes ECOG, y etapa de la enfermedad. La resección limitada se realizó con mayor frecuencia utilizando un enfoque mínimamente invasivo (62.1% versus 50, 9%, p < 0.001) y con tiempos de operación más cortos que los procedimientos extendidos (165 min versus 189 min, p <0.001), pero el mismo Clavien-Dindo ≥3 complicaciones postoperatorias (6, 44% versus 6, 43%, p = 0.99), mortalidad a los 30 días (0, 63% versus 0, 38%), resultados oncológicos y tasas de supervivencia (5-y OS 0, 84 versus 0, 83, 5-PFS 0, 85 versus 0, 84). LIMITACIONES: Existen limitaciones inherentes a la naturaleza retrospectiva del estudio y una posible falta de consistencia en el tratamiento entre centros a lo largo del tiempo. Las indicaciones de por qué se eligió una operación específica se basaron principalmente en crieterios de los cirujanos. CONCLUSIONES: La resección segmentaria es una opción de tratamiento segura y efectiva para el cáncer de la flexión esplénica. Consulte Video Resumen en http://links.lww.com/DCR/B307 . (Traducción—Dr. Adrian Ortega ) Abstract : Supplemental Digital Content is available in the text.